Pertanggung Jawaban Hukum Terhadap Pelaku Tindak Pidana Judi Online - Muhammad Yusuf; Wahyu Prawesthi; Sri Sukmana Dmayanti; Dedi Wardana Nasution (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2022)
The development of information technology has driven thetransformation of conventional gambling into a more complex digitalform, namely online gambling. This practice has become a seriousproblem in Indonesia because it not only harms individualseconomically and psychologically but also threatens social and legalstability. This study aims to analyze the legal regulations applicableto online gambling crimes and examine the mechanisms for lawenforcement in Indonesia. The method used is normative juridicalwith a statutory approach and case studies. The results show thatdespite the existence of several regulations such as the CriminalCode, Law No. 7 of 1974, and the Electronic Information andTransactions Law No. 11 of 2008 in conjunction with No. 19 of 2016,the implementation of law enforcement against online gamblingperpetrators still faces various obstacles, such as limited jurisdiction,technological constraints, and low public legal awareness. Therefore,regulatory reform, increased capacity of law enforcement officers,and cross-sector collaboration are needed to strengthen legalaccountability and the effectiveness of online gambling eradication inIndonesia.